A Complex Facial Trauma Case with Multiple Mandibular Fractures and Dentoalveolar Injuries - Yeliz Guven; Sevgi Zorlu; Abdulkadir Burak Cankaya; Oya Aktoren; Koray Gencay (Case Reports in Dentistry)
The principles of management of mandibular fractures differ in children when compared to adults and depend on the specific age-related status of the growing mandible and the developing dentition. This paper presents a case report with a complex facial trauma affecting the mandibular body and condyle region and dentoalveolar complex. Clinical examination revealed soft tissue injuries, limited mouth opening, lateral deviation of the mandible, an avulsed incisor, a subluxated incisor, and a fractured crown. CBCT examination revealed a nondisplaced fracture and an oblique greenstick fracture of the mandibular body and unilateral fracture of the condyle. Closed reduction technique was chosen to manage fractures of the mandible. Favorable healing outcomes on multiple fractures of the mandible throughout the 6-year follow-up period proved the success of the conservative treatment. This case report is important since it presents a variety of pathological sequelae to trauma within one case.